The dissolution of simulant vitrified intermediate level nuclear waste in young cement water. (2020) - Mann, Colleen; Eskelsen, Jeremy R.; Leonard, Donovan N.; Pierce, Eric; Corkhill, Claire L
Abstract: It is pertinent to the safety case for geological disposal in the UK that the behaviour of vitrified wastes in proximity to cementitious materials is understood. In this study, vitrified simulant intermediate level nuclear waste (ILW) was subject to dissolution in a synthetic cement water solution to simulate disposal conditions. Results show that the presence of alkali / alkaline earth elements in the cementitious solution can be favourable, at least in the short-term, leading to lower dissolution rates associated with incorporation of these elements into the altered layer of the glass.